Effect of Fly Ash on Soil Properties and Rice Productivity in an Inceptisol of Assam - A. Sharma and Bedanta Das, K.N. Das, D.K. Patgiri, A. Basumatary, K. Das (Journal of the Indian Society of Soil Science, 2015)
A field experiments was conducted in kharif season 2012 on an Inceptisol of Jorhat, Assam to study the effect of application of fly ash on yield of rice (Oryza sativa L.) and physicochemical properties of the soil. The results indicated that the treatments which received fly ash @ 5 and 15 t ha-1 alone recorded a yield increase of 23.3 and 32.4 per cent, respectively over absolute control. The highest rice yield (3.41 t ha-1) was achieved in treatment 50% RDF + FYM 5 t ha-1 + FA 15 t ha-1. On the other hand, fly ash applied @ 5 t ha-1 in combination with RDF 50% + FYM 5 t ha-1 produced 40.1 per cent more yield over absolute control. The addition of fly ash resulted in significant increase in pH, EC, organic C, CEC and available nutrient in the post-harvest soil. The study revealed fly ash as a suitable material for improving crop yield as well as soil fertility.